PREDIKSI TRANSFER PANAS RADIASI TERAHERTZ DALAM JARINGAN BIOLOGI MENGGUNAKAN METODE KOMPUTER ANALOG - Malik, Usman; Hamdi, Muhamad (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
THz spectrum falls between infrared and microwave regions of electromagnetic spectrum, and it shares some properties with each of this. Field change with thermoregulation rise is caused by absorption in tissue cell. It describes a dynamic behavior problem of THz heat transfer in tissue which it is derived using a modified bio-heat conduction equation for THz photons. The design and its solving use an analog computer method to predict temperature in tissue as a function of space at steady state and as a function of time during transient state. Test of modeling applies sub millimeter wavelengths in range from 0.3 mm to 3 mm. Results are compared to other numerical methods in a range close to far infrared for studying behaviors of its absorption in tissue and their thermal parameters. They perform for all are almost the same approach. The parameters obtained between model and experiment data are quite accurate with the uncertainty or a propagation error is 0.08 %. Keywords : analog computer; THz radiation; thermal distribution; absorption; tissue cell.